PENGGUNAAN PENGADUK STATIK UNTUK PENGURANGAN KEBUTUHAN KATALIS DALAM PRODUKSI BIODIESEL - Sri Purnama Sari, Armansyah H Tambunan, dan Lilik P EkoNugroho (Jurnal Teknologi Industri Pertanian, 2016)
Current technology for biodiesel production is a transesterification process of vegetable oil withmetanol in batch system with the help of catalyst. The technology faces many disadvantageous for large scale,such as the requirement for rigorous stirring and purification of the product from the catalyst. Previous studyshowed that utilization of static mixing reactor can enhance the reaction rate and reduce the requirement ofcatalyst and can be operated continuously. The objective of this study was to examine the role of static mixer inreducing the catalyst requirement for the transesterification process of biodiesel production in continuous mode.Palm oleinwas used as feedstock for the transesterification process with 1:6 of mole ratio to metanol at 65oCreaction temperature. Catalyst used for the experiment was KOH with variations of 0.3% and 0.5% to the oil fedinto the reactor and the numbers of static mixer modules were varied (1, 2, 3, 4, and 5 modules) to evaluate theireffects to the required catalyst. As expected, the experimental results confirmed a higher conversion of thereactionby the increasing number of the static mixer modules at a specific catalyst percentage. Highestconversions obtained with 5 moduleswere 92.5% (w/w) and 88.9% (w/w), for 0.3% and 0.5% of catalyst,respectively. Analysis to the experimental results showed that 0.1% of catalyst could be replaced by the additionof 0.9 modules of static mixer, which was equivalent to 58.1 cm length ofthe used static mixer configuration.Keywords:continuous mode of transesterification, static mixing module, catalyst reduction